Molten Salt Synthesis of Nanocrystalline ZnFe2O4 and Its Photocatalytic Dye Degradation Studies. (2017) - Preethi, G.; Ninan, Aashish S.; Kumar, Kiran; Balan, Ramdas; Nagaswarupa, H.P.
Abstract: Magnetically separable ZnFe2 O4 photocatalyst was prepared by facile Molten Salt Method (MSS) using eutectic mixture of NaCl- KCl flux. The obtained products were characterized by Powder X-ray diffraction (XRD) and Scanning electron microscopy (SEM). XRD confirm single phase ZnFe2 O4 formed at 900°C for 1 h. Crystalline size was calculated to be 50 - 90 nm using Scherrer expression. SEM micrographs shown particles crystallized in submicron range of polygonal morphology. The photocatalytic activity was evaluated for degradation of Rhodamine B (RhB) under UV irradiation, it found to show 98% of degradation.